Moving Towards The Common Goal of Collaborative Governance in Indonesia Amid The Endemic Covid-19 - Putra Anugerah Wibowo; Dian Suluh Kusuma Dewi (Universitas Medan Area, 2023)
This article aims to map the topics and issues of the Government of Indonesia's policies from the pandemic to the endemic of Covid-19. This study uses a qualitative approach. Data were obtained from literature such as online media and official government websites, laws and regulations and research journals related to Indonesian Government policies in the Covid-19 pandemic and then processed using the Nvivo 20 application. There were 251 articles reviewed and sourced from the Dimensions database. The data is processed using automatic coding and analyzed using the word cloud analysis and hierarchy chart features. The results of the study reveal that policies during the Covid-19 pandemic experienced easing. Policy easing is based on the declining results of Covid-19 cases and the increasingly controlled pandemic situation. The easing of this policy is that people are allowed homecoming, not wearing masks, domestic and foreign travellers with complete vaccines do not need to show antigen or PCR tests, face-to-face learning, and the lifting the Community Activity Restrictions (PPKM). The policies relaxed by the government are a transitional step from a pandemic to an endemic. Policy changes taken by the government require policy adaptation and coordination between governments at the central to regional levels.